THE MODEL FOR DEVELOPING THE VILLAGE HEATH VOLUNTEERS (VHVs) IN PROMOTING AND PREVENTING DISEASES AFTER THE COVID-19 SITUATION IN KHAO YOI DISTRICT, PHETCHABURI PROVINCE - Wetchakun, Gonkasan; Phueakbuakhao, Wipavanee (Journal of MCU Phetchaburi Review, 2025)
The objectives of this research were to: 1) study the factors of the roles and potential of village health volunteers (VHVs), 2) study the factors of the roles that affect the potential of village health volunteers (VHVs) in promoting public health care, and 3) propose a model for developing the potential of village health volunteers (VHVs) in Khao Yoi District, Phetchaburi Province. The sample group used in the research was 294 village health volunteers (VHVs) in Khao Yoi District, Phetchaburi Province, using stratified random sampling. The research instruments were questionnaires and interview forms. The statistics used for data analysis were percentage, mean, standard deviation, multiple regression analysis, and content analysis. The research results were as follows: 1) The factors of the roles and potential of village health volunteers (VHVs) in promoting public health care in Khao Yoi District, Phetchaburi Province were at a high level overall. 2) The overall factors of the roles, the roles of public health reporters between officers and villagers, the roles of public health service providers to the public, and the roles of advisors and knowledge transferrs, affected the potential of village health volunteers (VHVs) in promoting public health care in Khao Yoi District. Phetchaburi Province with statistical significance at the .05 level. 3) Potential development (VHV) by creating a work manual for VHV to be a guideline for operations to support the development of the potential of village health volunteers (VHV) to have knowledge and ability to perform their duties according to the specified standards efficiently. Keywords: Potential, Operation, Village health volunteers (VHV), Phetchaburi